2021
DOI: 10.1002/smll.202103613
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Grown CoMn2O4 3D‐Tetragons on Carbon Cloth: Flexible Electrodes for Efficient Rechargeable Zinc–Air Battery Powered Water Splitting Systems

Abstract: oxygen evolution reaction and oxygen reduction reaction (OER and ORR) play important roles in rechargeable zinc-air battery (ZAB), whereas OER and hydrogen evolution reaction (HER) are the core reactions in EWS. [4,5] These electrochemical reactions exhibit sluggish kinetics because they require multistep protoncoupled electron transfers, which increase the overpotentials of the systems, thus causing the losses of considerable energy and long-term electrocatalytic activity. [6][7][8][9] Multifunctional electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 108 publications
(144 reference statements)
0
31
0
Order By: Relevance
“…In the reported reaction system, activated CC is used as a conductive substrate that simultaneously guarantees great electron transfer and physical integration of freestanding electrodes; 36 2-aminoterephthalic acid (NH 2 -TPA), a regular ligand to build metal-organic frameworks (MOFs), 37 is expected to act as spatial isolators when the dosage is far from complete for growing MOF crystals, in which they coordinate with Co/Ni ions and form hybrid metal sites in a high-dispersion manner. As for the intended addition of glucose, the hydrolysis of glucose that occurred during the hydrothermal process can generate acids 38 that interfere with the growth of Co/Ni-TPA MOFs, whereas glucose-derived polymers that have greater infinity to CC than metal ions would deposit on the external surface of CC fibers and in situ react with metal species, 39 forming NiCoO/carbon composite layers on CC fibers. The insufficient coordination between Co/Ni ions and NH 2 -TPA assisted by the strong interaction between Co/Ni ions and glucose-derived polymers, jointly induces the growth of amorphous NiCoO highly dispersed in the carbon matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the reported reaction system, activated CC is used as a conductive substrate that simultaneously guarantees great electron transfer and physical integration of freestanding electrodes; 36 2-aminoterephthalic acid (NH 2 -TPA), a regular ligand to build metal-organic frameworks (MOFs), 37 is expected to act as spatial isolators when the dosage is far from complete for growing MOF crystals, in which they coordinate with Co/Ni ions and form hybrid metal sites in a high-dispersion manner. As for the intended addition of glucose, the hydrolysis of glucose that occurred during the hydrothermal process can generate acids 38 that interfere with the growth of Co/Ni-TPA MOFs, whereas glucose-derived polymers that have greater infinity to CC than metal ions would deposit on the external surface of CC fibers and in situ react with metal species, 39 forming NiCoO/carbon composite layers on CC fibers. The insufficient coordination between Co/Ni ions and NH 2 -TPA assisted by the strong interaction between Co/Ni ions and glucose-derived polymers, jointly induces the growth of amorphous NiCoO highly dispersed in the carbon matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…TEM analysis showed that the high content (mass loading) of Fe and N in the porous structure of N-OMC enhanced the ORR active areas. Zhang et al created the pores in the carbon matrix by the heat treatment of macrocyclic cucurbit [6]uril (CB [6]) and M-N-C precursors. 76 They conrmed the N-doped carbon pore structure with Fe-bond through the HAADF-STEM images.…”
Section: M-n-c Electrocatalystsmentioning
confidence: 99%
“…4 Therefore, the environmentally friendly energy conversion and storage devices such as fuel cells, electrochemical water-splitting systems, and metal-air batteries have been widely studied due to their clean property. 5,6 With respect to the metal-air batteries, this system can be operated without pre-storing oxygen in the cells. It is noteworthy to mention that oxygen can be taken directly from the ambient air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most of the practically available water electrolyzers work in strong acid or alkaline electrolytes . The optimal working conditions for HER electrocatalysts and OER electrocatalysts are quite different, which leads to the difficult assembly and increased cost of the electrolyzers. , Therefore, the development of the efficient electrocatalysts with HER/OER bifunctional activity from low-cost materials is highly desirable for simplifying the system and reducing the cost of the practical water electrolyzers. To date, although some of the reported bifunctional electrocatalysts have been applied in overall water splitting, there are still challenges hindering their application and remaining to be solved.…”
Section: Introductionmentioning
confidence: 99%